2016
DOI: 10.1002/2015jd024702
|View full text |Cite
|
Sign up to set email alerts
|

Surface dimming by the 2013 Rim Fire simulated by a sectional aerosol model

Abstract: The Rim Fire of 2013, the third largest area burned by fire recorded in California history, is simulated by a climate model coupled with a size‐resolved aerosol model. Modeled aerosol mass, number, and particle size distribution are within variability of data obtained from multiple‐airborne in situ measurements. Simulations suggest that Rim Fire smoke may block 4–6% of sunlight energy reaching the surface, with a dimming efficiency around 120–150 W m−2 per unit aerosol optical depth in the midvisible at 13:00–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…Also, observational datasets looking at the vertical distribution of BrC in the atmosphere would help to determine whether the model is simulating similar processes to observations. This includes more information regarding the transport of BrC to upper levels by deep convection, and the in-cloud aqueous production of BrC (Zhang et al, 2017). GFED emission inventory accuracy is also important because the reported fuel type and location play a role in the model vertical injection heights of carbonaceous aerosols.…”
Section: Discussionmentioning
confidence: 99%
“…Also, observational datasets looking at the vertical distribution of BrC in the atmosphere would help to determine whether the model is simulating similar processes to observations. This includes more information regarding the transport of BrC to upper levels by deep convection, and the in-cloud aqueous production of BrC (Zhang et al, 2017). GFED emission inventory accuracy is also important because the reported fuel type and location play a role in the model vertical injection heights of carbonaceous aerosols.…”
Section: Discussionmentioning
confidence: 99%
“…Theory and previous analyses have also demonstrated that wildfire smoke can reduce the amount of solar radiation that reaches the Earth's surface through a combination of absorption and scattering of radiation by the aerosols that comprise wildfire smoke (Robock, 1988(Robock, , 1991Stone et al, 2011;Yu et al, 2016;Zhang et al, 2016). Precise comparisons of the magnitude of smoke's effect on solar radiation among studies are hampered by methodological differences such as solar zenith angle (i.e., season and time of day) and AOT measurement; nonetheless, our estimate of a 121-W m À2 reduction in solar radiation per 1.0 AOT is similar Note.…”
Section: Smoke Effects On Solar Radiation and Air Temperaturementioning
confidence: 97%
“…However, indirect evidence suggests that wildfire smoke has the potential to cool river water temperatures. Wildfire smoke particles scatter and absorb incoming solar radiation (Robock, 1988(Robock, , 1991Stone et al, 2011), reducing the amount of solar radiation that reaches the Earth's surface (Yu et al, 2016;Zhang et al, 2016), and can consequently reduce air temperatures (Robock, 1988(Robock, , 1991Stone et al, 2011;Zhang et al, 2016). Solar radiation and air temperature are important drivers of stream and river water temperatures (Beschta et al, 1987;Caissie, 2006;Johnson, 2004); therefore, wildfire smoke may have the capacity to cool lotic water temperatures.…”
Section: 1029/2018wr022964mentioning
confidence: 99%
“…Wildfires are responsible for emitting large quantities of smoke, which can have significant impacts on air quality (Ignotti et al, 2010), radiative fluxes (Robock, 1988;Stone et al, 2011;Yu et al, 2016), visibility (Achtemeier, 2009), and cloud microphysics (Kaufman & Nakajima, 1993). Smoke from wildfires can also promote daytime surface cooling by blocking sunlight (Robock, 1988).…”
Section: Introductionmentioning
confidence: 99%